2018
DOI: 10.1002/ijc.31569
|View full text |Cite
|
Sign up to set email alerts
|

Rab37 in lung cancer mediates exocytosis of soluble ST2 and thus skews macrophages toward tumor‐suppressing phenotype

Abstract: Interplay between cancer epithelial cells and the surrounding immune cells shape the tumor microenvironment to promote cancer progression. Tumor-associated macrophages are well recognized for their roles in cancer progression. Accumulating evidence also indicates implication of Rab small GTPase-mediated exocytosis in tumorigenesis. However, the mechanism for Rab-mediated exocytosis in regulation of macrophage polarization is not clear. We have previously identified Rab37 as a metastasis suppressor in lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Meanwhile, GBP5 expression in CM is associated with favorable prognosis (Wang et al, 2018). RAB37 , as a tumor suppressor gene, promotes M1-like macrophage infiltration and suppresses tumor growth (Tzeng et al, 2018), and it was frequently down-regulated due to promoter hypermethylation in metastatic lung cancer, can serve as a potential predictive biomarker (Wu et al, 2009). RAB37 -mediated SFRP1 secretion suppresses cancer stemness, and dysregulated RAB37-SFRP1 pathway confers cancer stemness via the activation of Wnt signaling (Cho et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, GBP5 expression in CM is associated with favorable prognosis (Wang et al, 2018). RAB37 , as a tumor suppressor gene, promotes M1-like macrophage infiltration and suppresses tumor growth (Tzeng et al, 2018), and it was frequently down-regulated due to promoter hypermethylation in metastatic lung cancer, can serve as a potential predictive biomarker (Wu et al, 2009). RAB37 -mediated SFRP1 secretion suppresses cancer stemness, and dysregulated RAB37-SFRP1 pathway confers cancer stemness via the activation of Wnt signaling (Cho et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive feedback loop of interaction between CSCs with M2 cells in which CSCs secrete TGF-β to stimulate M2 cells for secreting IL-37 that, in turn, potentiates self-renewal, pluripotency, and invasive features of CSCs, as shown in pancreatic cancer (Sainz et al, 2015). and induce M2 polarization (Tzeng et al, 2018). In addition, IL-6 release from CSCs is important not only for sustaining their stemness (self-renewal) but also for activating Tregs, inactivating CTLs and inducing macrophage polarity toward a protumor M2-like phenotype (L. Kato et al, 2018;Lytle et al, 2018;Su et al, 2018).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…We have previously reported that Rab37 mediates exocytosis of several secretion factors in non-small cell lung (NSCLC) cells 18 , 19 . In addition, Rab37 facilitates soluble IL-1 receptor-like protein secretion in NSCLC cells to antagonize IL-33-mediated M2 macrophage polarization in TME 20 . To date, the role of Rab37 in tumor-infiltrating immune cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%